Heat shock treatment with mild electrical stimulation safely reduced inflammatory markers in healthy male subjects - Kondo, Tatsuya; Sasaki, Kazunari; Adachi, Hironori; Nakayama, Yoshiharu; Hatemura, Masahiro; Matsuyama, Rina; Tsuruzoe, Kaku; Furukawa, Noboru; Motoshima, Hiroyuki; Morino (Koga), Saori; Yamashita, Yasuyuki; Miyamura, Nobuhiro; et al. (Obesity research & clinical practice, 2010)
Obesity induces chronic inflammation, which contributes to the development and progression of insulin resistance, diabetes and atherosclerosis. We have recently shown that induction of heat shock protein 72 by mild electric current and thermo (MET) treatment in mouse model of type 2 diabetes ameliorated glucose homeostasis and insulin resistance accompanied by reduced adiposity. For clinical application of MET, we confirmed its safety in healthy subjects. MET was applied for 10 healthy Japanese male (12 V, 55 pulses/s, 30 min at 42 °C) twice a week for 8 weeks. Fat volume was measured by CT scan and several parameters were investigated. MET did not induce any adverse effects nor muscle contraction/pain. There were no significant alterations in glucose homeostasis or insulin resistance. Visceral and subcutaneous fat volume showed a trend of decrease without significant difference (−3.9% and −4.3%, respectively), which were restored 8 weeks after withdrawal of MET. Interestingly, serum tumor necrosis factor-α (TNF-α: 0.91 ± 0.05 pg/mL vs. 0.67 ± 0.06 pg/mL; p = 0.006) and high sensitivity C-reactive protein (hs-CRP: 521.9 ± 73.9 ng/mL vs. 270.8 ± 43.7 ng/mL; p = 0.023) levels, both of which are associated with chronic inflammation, were significantly decreased. MET may be beneficial for the reduction of an inflammatory response observed in diabetes and metabolic syndrome.